Occupational-related chemical ocular injuries: an analysis of 82 patients - Kivanc, Sertac Argun; Budak, Berna Akova; Cevik, Sadik Gorkem; Baykara, Mehmet; Yasar, Sefa; Ozmen, Ahmet Tuncer (The European Research Journal, 2016)
Objectives. To investigate the  characteristics of occupational chemical eye injuries. Methods. Medical records of patients, who were registered to hospital officially as occupational chemical eye injuries between January 2010 and December 2013, were reviewed. The age, gender, injured eye, chemical agent, nature of the chemical, ocular findings, emerging complications and the information whether the patients knew the chemical agent causing the injury was recorded. Results. One hundred one eyes of 82 patients (2 women, 80 men) were included in the study. The mean age of the patients was 32.9±8.6 years (range: 19-59 years). Injury was bilateral in 19 patients. Chemical agents were not known by 53% of the patients. The most known agents were caustic agents (23%). Sulfuric acid (9%) and calcium hydroxide (4%) were other known chemical agents. The most common injury was superficial punctate epitheliopathy. Ten eyes of 9 patients had corneal edema. This injury was caused by acidic agents in 5 and alkaline agents in 3 patients. Corneoscleral perforation accompanied by chemical injury in one patient with car battery explosion. Conclusions. Most of the workers, who had eye injuries with chemicals, do not know the nature of chemical agent which caused the injury. Ocular morbidities may be decreased with the education of the workers about chemicals, working environment and protective measures.